Awareness of radiation hazards and knowledge of radioprotective measures among radiologists and non-radiology staff: a cross-sectional survey - Jehad Fataftah; Raed Tayyem; Salem Al-Dwairy; Abdel Rahman Al Manasra; Aqleh Ibrahim; Randa Al Ryalat; Mallak Alwreikat; Hebatuallah Al-Shraah; Razan Alharbi; Banan Alharbi (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background Ionizing radiation has become increasingly utilized in medical practice. Consequently, healthcare workers must be aware of radiation hazards and apply the necessary countermeasures to reduce occupational exposure. This study assessed the awareness of radiation hazards and knowledge of radiation protection measures among radiologists and non-radiologists. These findings may improve the application of various safety measures during medical interventions involving radiation. Methods We conducted a cross-sectional questionnaire-based study among 200 medical personnel, including consultant surgeons, physicians, radiologists, nurses, and radiographers, across five hospitals in Jordan between November 2022 and February 2023. The questionnaire collected data on demographic characteristics, awareness of radiation hazards, and knowledge of radioprotective techniques. Results Overall, the knowledge of radiation protection and awareness of radiation hazards among the participants were poor (51.55% and 37.17%, respectively). No significant difference was detected between the medical disciplines in terms of the level of knowledge of radiation protection; however, radiographers were significantly more aware of radiation hazards. Conclusions According to our findings, medical personnel generally have poor awareness of radiation hazards and radiation protection protocols. However, this understanding can be enhanced through periodic in-service training and regular monitoring of occupational radiation exposure by health professionals.